Prinsip Paritas Partisipasi dalam Midah Simanis Bergigi Emas Analisis Wacana Perspektif Feminisme Kritis - Jagad Wijaksono; Viono, Tono (Imajeri: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Through the representation of the character Midah, Pramoedya brings the discourse of gender subordination as the main epicenter of the story's conflict. This study aims to look at the relationship of female leaders with social justice based on the principle of participation parity. The approach used is a qualitative interpretation with the discourse analysis method. The findings will be processed with the literature on participation parity in critical feminism theory. The findings show the form of injustice received by Midah's character in the dimensions of misrecognition, misrepresentation, and misrepresentation. Each character shows the strategy for resolution of injustice through action, self-image and the courage to survive.